Highly porous honeycomb manganese oxide@carbon fibers core–shell nanocables for flexible supercapacitors. (April 2015) - Zhang, Deyang; Zhang, Yihe; Luo, Yongsong; Chu, Paul K.
Abstract: Core–shell electrodes composed of highly porous honeycomb manganese oxide@carbon fibers (HMO@CFs) are synthesized by a facile hydrothermal approach involving an in situ redox replacement reaction between potassium permanganate (KMnO4 ) and carbon fibers. In this reaction, the carbon fibers serve as not only a sacrificial reductant, but also the substrate. The porous HMO@CFs core–shell nanocables deliver remarkable electrochemical performance with a high capacitance (295.24 F g −1 at 100 mA g −1 ), high good rate capability, and superior cycling stability (about 96.4% specific capacitance retained after 3000 cycles). The maximum energy density of 22.2 W h kg −1 (at a power density of 400 W kg −1 ) and power density of 12, 000 W kg −1 (at an energy density of 10 W h kg −1 ) can be achieved at an operating voltage of 1.6 V. The fabrication method is simple, cost-effective, and readily scalable thereby having large commercial potential. Graphical abstract: Core/shell electrodes composed of highly porous honeycomb manganese oxide@carbon fibers (HMO@CFs) are synthesized hydrothermally using an in situ redox replacement reaction between potassium permanganate (KMnO4 ) and carbon fibers. The materials deliver excellent performance in flexible supercapacitors boasting high specific capacity and stability. Highlights: Highly porous honeycomb-like manganese oxide@carbon fibers core–shell materials are introduced into the anode of SCs. Excellent electrochemical performance and flexible mechanical properties are obtained. The simple and economical approach enables the design of hybrid electrode architectures for flexible energy storage devices.